A Hotelling Model for Fixed-Cost Driven Power Generation - Andreas A. Renz; Christoph Weber (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2013)
This paper links Hotelling's theory, in recent literature applied to an emission constrained environment, with the classical capacity planning framework to describe portfolio time-paths in electricity production. Emission targets are considered by a ceiling on the stock of pollution. We propose conditions for an efficient production portfolio as a subset of available technologies. We then derive potential production portfolio time-paths for a renewable, a fossil and a carbon capturing technology that differ according to their fixed and variable costs, their efficiency and their polluting characteristics. We conclude that the share of the fossil technology will continuously decrease, the scarce resource will be fully exploited. On each constrained path, the stock of pollution will remain at the ceiling for a non-zero time period. Emission targets push down scarcity rents, an option for carbon capturing would decrease societal costs and uphold scarcity rents.
Keywords: C61; Q32; Q41; L94; 330; Scarce resources; Optimal control theory; Hotelling; Valuation; Non-renewable resource; Pollution target; Climate change; Peak-load-pricing